LGBTQIAP+ bodies and practices: from censorship to capital presence - Lima, Sued; Oliveira, Taís de (Estudos Semióticos, 2022)
In Brazil, for most of the 20th century, homosexual bodies and  practices were constantly repressed in the streets and censored in newspapers,  literature, or cinema. Although the organization and establishment of social  movements occurred during this period, the prevalence of conservative morals  contributed to the promotion of discriminatory actions by part of civil society  and the State. Nowadays, with the evidence of social movements and the  growing concern with identity agendas, the emergence of discourses that  promote homosexuals’ recognition seeks to meet social and media demands. The  first refer to the social inclusion of this minority group that, historically, is  constituted as a "concessive identity" (OLIVEIRA, 2021) in relation to  heteronormative identity constructions, which are implicative. The second  correspond to market and media interests that adapt to social demands and give  rise to practices such as Pink Money and the insertion of homosexual characters  in various spheres of communication. In order to address these socio-cultural  and media transitions, we mobilize concepts from discourse semiotics to  contrast homosexual repression in opinion articles from the newspaper Lampião  da Esquina (1978-1981) with the numerous presence of LGBTQIAP+ in  contemporary media productions, such as reality shows and TV shows in general.